AB0772 Exploring Fatigue Patterns over Time in Early Osteoarthritis: Results from the CHECK Study. (10th June 2014) - Bode, C.; Botterman, J.; Siemons, L.; Van de Laar, M.; Dekker, J.
Abstract : Background: Only a few studies have examined fatigue in Osteoarthritis, but all revealed fatigue as ubiquitously present and related to several physical and mental health aspects among OA patients. Objectives: The goal of this study was to examine whether different groups of fatigue trajectories can be identified among middle-age patients with early symptomatic osteoarthritis (OA), to establish the level of fatigue severity within each of these fatigue groups, and to assess the role of age, gender and OA severity in relation to group classification. Methods: Data on fatigue and patient characteristics were collected from the CHECK cohort. Growth mixture modeling (GMM) was applied in order to identify distinct fatigue groups as well as to take into account the influence of radiographic OA severity (Kellgren-Lawrence grading), age and gender on group classification. Results: A stable, a U-shape, and an inverted U-shape trajectory were identified. The fatigue levels of the latter two groups (i.e. approximately two-thirds of the sample) were comparable to the Dutch cancer population. Females and younger OA patients experienced higher levels of fatigue within each group and females were more likely than males to exhibit the inverted U-shape fatigue pattern. The covariates were not related to the interindividual differences in fatigue change over time within each fatigue group. Conclusions: Three different fatigue patterns were found among a sample of early OA patients. These patterns indicate that a large number of OA patients experience elevated levels of fatigue already at an early stage of OA. This finding asks for more attention regarding fatigue in OA research, and warrants tailored psychosocial interventions for patients with elevated levels of fatigue. Acknowledgements: The CHECK study is financed by the Dutch Arthritis Foundation. Disclosure of Interest: None declared DOI: 10.1136/annrheumdis-2014-eular.5062